LAS HORMIGAS DEL VALLE DE TEHUACÁN (HYMENOPTERA: FORMICIDAE): UNA COMPARACIÓN CON OTRAS ZONAS ÁRIDAS DE MÉXICO - Rios-Casanova, Leticia; Valiente-Banuet, Alfonso; Rico-Gray, Victor (Instituto de Ecología, A.C., 2004)
Ants are considered an important aspect of arid zones mainly due to their role in structuring plant communities and for the diverse interactions they establish with other organisms. However in Mexican arid zones a basic understanding of ant species diversity is lacking. In this study we examined the ant fauna of a locality situated in the semi-desert Tehuacán Valley (San Rafael Coxcatlán). Our objectives were to estimate ant species richness within this region and to obtain a more extensive survey of the Tehuacán Valley by combining our data with another study. Finally we compared the species richness of this Valley to that of other Mexican arid zones (Mapimí, Durango, Chihuahuan Desert and Los Horcones, Sonora, Sonoran Desert). Ants of San Rafael Coxcatlán were collected between November 1999 and January 2001 using pitfall traps. 28 ant species were captured from 14 genera within five subfamilies, which is a high species richness for a small area (5 km²). Based on a cluster analysis, the mirmecofauna of Los Horcones and the Tehuacán Valley were the most similar; both areas have ant species with broad distribution as well as some of tropical affinity such as Pseudomyrmex major and Camponotus atriceps. Similar patterns have been reported for the vegetation, birds and mammals in both areas; several genera are shared, most of them of tropical affinity. This work represents one of the first efforts to understand ant diversity in an arid zone of central Mexico.